Mouse Inscuteable Induces Apical-Basal Spindle Orientation to Facilitate Intermediate Progenitor Generation in the Developing Neocortex - Postiglione, Maria Pia (Cell Press, 2011)
Neurons in the mammalian neocortex arise from asymmetric divisions of progenitors residing in the ventricular zone. While in most progenitor divisions, the mitotic spindle is parallel to the ventricular surface, some progenitors reorient the spindle and divide in oblique orientations. Here, we use conditional deletion and overexpression of mouse Inscuteable (mInsc) to analyze the relevance of spindle reorientation in cortical progenitors. Mutating mInsc almost abolishes oblique and vertical mitotic spindles, while mInsc overexpression has the opposite effect. Our data suggest that oblique divisions are essential for generating the correct numbers of neurons in all cortical layers. Using clonal analysis, we demonstrate that spindle orientation affects the rate of indirect neurogenesis, a process where progenitors give rise to basal progenitors, which in turn divide symmetrically into two differentiating neurons. Our results indicate that the orientation of progenitor cell divisions is important for correct lineage specification in the developing mammalian brain.